Analisis Serangan ARP Poisoning pada Jaringan Hotspot Berbasis MikroTik Menggunakan Bit-Twist - Dimas Wiryatari (Jurnal Tata Kelola dan Kerangka Kerja Teknologi Informasi, 2026)
ABSTRACT – The security of MikroTik-based hotspot networks still has potential vulnerabilities, particularly in the Address Resolution Protocol (ARP), which operates on a trust-based mechanism without authentication. This study aims to analyze ARP Poisoning attacks on MikroTik-based hotspot networks using Bit-Twist as a tool to generate forged ARP packets. The research method was conducted through experimental scenarios by observing changes in ARP cache entries on the client side and analyzing the impact of the attack on network quality of service, including delay and packet loss parameters. The results show that ARP Poisoning attacks cause modifications in the client ARP cache, enabling traffic redirection through the attacker’s device. In addition, the attacks lead to increased delay and packet loss in the hotspot network. These findings indicate that MikroTik-based hotspot networks are vulnerable to ARP Poisoning attacks if additional security mechanisms are not implemented, highlighting the need for stricter security configurations to mitigate similar attacks.. Keywords – ARP Poisoning; Bit-Twist; MikroTik; Hotspot; ARP Cache.